Arsenic in Drinking Water in Bangladesh: Factors Affecting Child Health - Aziz, Sonia N.; Aziz, Khwaja M. S.; Boyle, Kevin J. (Frontiers in Public Health, 2014)
The focus of this paper is to present an empirical model of factors affecting child health by observing actions households take to avoid exposure to arsenic in drinking water. Millions of Bangladeshis face multiple health hazards from high levels of arsenic in drinking water. Safe water sources are either expensive or difficult to access, affecting people’s individuals’ time available for work and ultimately affecting the health of household members. Since children are particularly susceptible and live with parents who are primary decision makers for sustenance, parental actions linking child health outcomes is used in the empirical model. Empirical results suggest that child health is significantly affected by the age and gender of the household water procurer. Adults with a high degree of concern for children’s health risk from arsenic contamination, and who actively mitigate their arsenic contaminated water have a positive affect on child health.